Prognostic value of Doppler echocardiographic coronary flow velocity assessment at rest in elderly patients - Zagatina, Angela; Kalinina, Elena; Caprnda, Martin; Gaspar, Ludovit; Gazdikova, Katarina; Ullrich, David; Prosecky, Robert; Rodrigo, Luis; Kruzliak, Peter (Acta cardiologica, 2023)
BACKGROUND: Atherosclerosis and coronary artery disease (CAD) are a common condition and cause of death in the elderly population. There are difficulties with risk assessment in the elderly as the objectification of their symptomatic status can be challenging due to neuromuscular weakness, physical deconditioning or neurological, orthopaedic, peripheral vascular, or respiratory limitations. Non-invasive coronary artery velocity assessment by Doppler method at rest could be helpful in the elderly population. To evaluate the prognostic role of coronary artery ultrasound assessment in a non-selected elderly population in everyday clinical practice. METHODS: One hundred forty-five patients, aged ≥75years (99 women; 80 ± 4 years), formed the study group. Left coronary artery flows were scanned in addition to conventional echocardiography. During a median follow-up of 26 months, 16 deaths and 2 non-fatal MI occurred. RESULTS: In multivariable analysis, maximal coronary velocity was the only independent predictor for mortality (heart rate [HR]: 1.02, 95%, CI: 1.01-1.04, p < .0005) and for mortality/MI (HR: 1.02, 95%, CI: 1.01-1.03, p < .0001). The value of 110 cm/s maximal coronary flow velocity (CFL) in the proximal segments of left arteries was the best predictor for death, sensitivity 50%, specificity 90%, p < .005. The annual mortality rate was 16.6% persons/year for patients with elevated CFL ≥110 cm/s. The value 81 cm/s was the best predictor for death/MI, sensitivity 61%, specificity 80%, p < .0005; annual mortality rate was 11.2% persons/year for patients with elevated CFL ≥81 cm/s (p < .0001). CONCLUSION: Doppler CFL scanning during routine echocardiography is a feasible and valuable tool for assessment of short-term prognosis in elderly patients.
Keywords: prognóza; echokardiografie; rychlost toku krve; koronární cirkulace; Prognosis; Echocardiography, Doppler; Blood Flow Velocity; lidé; Female; senioři; Coronary Circulation; nemoci koronárních tepen; Aged; dopplerovská echokardiografie; ženské pohlaví; Echocardiography; Coronary Artery Disease; Humans